Влияние наноразмерного модификатора на основе зол гидроудаления омской тэц на свойства цементного камня - Anatoliy Fedorovich Kosach; Marina Alekseevna Raschupkina; Irina Nikolaevna Kuznetsova (Вестник СибАДИ, 2017)
Use of the nanodimensional modifier on the basis of the evils of hydroremoval of Omsk combined heat and power plant in a cement stone is presented in article and its physicomechanical properties are defined. The cement stone with use of nanodisperse zolotsementny mix in an optimum proportion is investigated. Application of the activated evils of hydroremoval as the ultradisperse zolotsementny knitting for industrial and civil engineering is proved. Physic mechanical indicators of a cement stone and cement and sand solution at a dry way of activation of ZShO of hydroremoval are presented.